2007
DOI: 10.2308/acch.2007.21.2.137
|View full text |Cite
|
Sign up to set email alerts
|

PCAOB Inspections of Smaller CPA Firms: Initial Evidence from Inspection Reports

Abstract: We examine 316 Public Company Accounting Oversight Board (PCAOB) inspection reports issued to smaller CPA firms (100 or fewer issuer clients) through July 2006. We find that 60 percent of the inspected firms have audit deficiencies. Firms with audit deficiencies are smaller, have a larger number of issuer clients, and are growing more rapidly than firms without deficiencies, suggesting an over-extension into the issuer client market by some firms. Deficiencies are more likely for inspections conducted in 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
94
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 4 publications
13
94
1
1
Order By: Relevance
“…A similar trend can be identified for the PCAOB inspections as the number of identified deficiencies decreased for triennially (Anantharaman, 2012;Hermanson et al, 2007;Landis, Jerris, & Braswell, 2011; and annually inspected firms (Church & Shefchik, 2012). In addition, the percentage of firms with quality control problems decreased , while the number of clean inspection reports increased Offermanns & Peek, 2011).…”
Section: Opening the Black Box Through Methodological Pluralismsupporting
confidence: 71%
See 2 more Smart Citations
“…A similar trend can be identified for the PCAOB inspections as the number of identified deficiencies decreased for triennially (Anantharaman, 2012;Hermanson et al, 2007;Landis, Jerris, & Braswell, 2011; and annually inspected firms (Church & Shefchik, 2012). In addition, the percentage of firms with quality control problems decreased , while the number of clean inspection reports increased Offermanns & Peek, 2011).…”
Section: Opening the Black Box Through Methodological Pluralismsupporting
confidence: 71%
“…Studies on the PCAOB regime use different approaches to categorize PCAOB reports into "good" and "bad". While several studies consider all identified deficiencies to be of economically equivalent importance and classify the reports according to the number of deficiencies (Hermanson, Houston, & Rice, 2007;Lennox & Pittman, 2010;Offermanns & Peek, 2011) or the rate of deficiencies , other studies distinguish between the kind of deficiency or between the degree of severity of the inspected deficiencies Robertson & Houston, 2010).…”
Section: Recognition Of Pcaob Inspections For Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work investigates differences in audit quality across firms whose auditors are subject to PCAOB inspections (or not) using variation in inspections of non-U.S. auditors (e.g., Lamoreaux, 2013;Fung et al, 2014;Krishnan et al, 2014;Shroff, 2015) as well as the effects of inspection reports (including their content such as unfavorable findings) on equity prices, audit quality, and client responses (e.g., Hermanson et al 2007;Lennox and Pittman, 2010;DeFond and Lennox, 2011;Gramling et al, 2011;Offermanns and Peek, 2011;Abbott et al, 2013;Gunny and Zhang, 2013;Boone et al, 2014;Acito et al, 2016;DeFond and Lennox, 2016). In addition, there is evidence on market reactions and client responses to PCAOB sanctions against Deloitte & Touche in 2007(e.g., Dee et al, 2011Boone et al, 2014).…”
mentioning
confidence: 99%
“…Roybark (2006) compares triennial firm and annual firm inspection reports issued by the PCAOB in 2005 and documents the types of deficiencies found on the inspection reports, but does tabulate the Since 2006, the PCAOB has begun publicly criticizing auditors for conducting too much work rather than not enough work (Palmrose 2006;Glover et al 2009), and so the reports analyzed by Roybark (2006) and Hermanson et al (2007) may reflect different areas of deficiencies than newer reports as a consequence of this shift in philosophy. This study examines all PCAOB inspections reports issued between 2005 and 2008.…”
Section: Introductionmentioning
confidence: 99%